PENGARUH NATRIUM SILIKAT PADA BETON PCC DENGAN PENAMBAHAN ARANG 2% TERHADAP KUAT TEKAN DAN POROSITAS - Fikri Fauzi Nur Alam; Muhammad Sihab; Y Djoko Setiyarto (CRANE: Civil Engineering Research Journal, 2026)
The use of sustainable materials in concrete is important to reduce dependence on conventional constituents without compromising material performance. This study investigated the effect of biochar and sodium silicate (Na₂SiO₃) on the compressive strength and porosity of Portland Composite Cement (PCC) concrete. The objective was to analyze the influence of 2% biochar and sodium silicate contents of 5%, 10%, and 15%, and to determine the optimum sodium silicate dosage. An experimental laboratory method was employed using cylindrical specimens measuring 150 × 300 mm. Compressive strength was tested at 7, 14, and 28 days, while porosity was measured at 28 days. The results showed that 5% sodium silicate provided the best performance, with a 28-day compressive strength of 16.49 MPa and the lowest porosity of 1.48%. The addition of 2% biochar alone was not sufficient to improve the 28-day compressive strength. Therefore, 5% sodium silicate was identified as the optimal dosage for producing PCC concrete with a denser internal structure and competitive mechanical performance.